1997
DOI: 10.1172/jci119321
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of genetic polymorphism in the renin-angiotensin system to the development of renal complications in insulin-dependent diabetes: Genetique de la Nephropathie Diabetique (GENEDIAB) study group.

Abstract: Diabetic nephropathy is a glomerular disease due to uncontrolled diabetes and genetic factors. It can be caused by glomerular hypertension produced by capillary vasodilation, due to diabetes, against constitutional glomerular resistance. As angiotensin II increases glomerular pressure, we studied the relationship between genetic polymorphisms in the renin-angiotensin system-angiotensin I converting enzyme (ACE), angiotensinogen (AGT), and angiotensin II, subtype 1, receptor-and the renal involvement of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
177
2
6

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(198 citation statements)
references
References 69 publications
13
177
2
6
Order By: Relevance
“…Evidence was found that inter-individual variation in the RAS genes contributes to a hypertension risk. Marre et al (1997) studied the contribution of genetic polymorphism in RAS to the development of renal complications in insulin-dependent diabetes in a European population.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence was found that inter-individual variation in the RAS genes contributes to a hypertension risk. Marre et al (1997) studied the contribution of genetic polymorphism in RAS to the development of renal complications in insulin-dependent diabetes in a European population.…”
Section: Discussionmentioning
confidence: 99%
“…Last, ACE inhibition prevents or retards diabetic nephropathy. [11][12][13] We suggested a dominant effect of the ACE D allele on the risk of diabetic nephropathy 3 and protection with the II genotype due to low plasma ACE levels. In experimental diabetes, high blood glucose causes high intraglomerular hydraulic pressure, glomerular filtration rate (GFR), and renal plasma flow, 7 just as in type 1 diabetes.…”
mentioning
confidence: 95%
“…2,3 Family studies suggest that this may be due to differences in their genetic backgrounds. 4,5 The angiotensin I-converting enzyme (ACE) gene was tested for its association with diabetic nephropathy for several reasons.…”
mentioning
confidence: 99%
“…7). Studies have found that the DD genotype is associated with a more rapid loss of renal function in diabetic nephropathy, 23 IgA nephropathy 24 and adult polycystic kidney disease, 25 when compared to the II or DI genotypes. The genotype does not appear to initiate or cause renal disease per se; rather it is associated with more rapid loss of renal function after disease development.…”
Section: Discussionmentioning
confidence: 99%